Pressupostos Pedagógicos e Teológicos da EBD da Igreja Batista: Uma Leitura Crítica da Proposta de LÉCIO DORNAS a partir de PAULO FREIRE e JUAN LUIS SEGUNDO. - Daneluz, Abigail Albuquerque de Souza (2010)
When we look at the records of Sunday School in Brazil, with exception of the material produced and brought by North American missionaries, until very recently, only one Baptist Brazilian, Lécio Dornas, had produced literature which aided pastors, leaders and teachers in the tough task of Christian teaching. In his trilogy: Help I m a Sunday School Teacher from 1997, Defeating the Sunday School Enemies from 1998 and The New Sunday School, The Usual Sunday School from 2001, Dornas introduces teachers to new possibilities on Sunday School. Nonetheless, in its pedagogical and theological tenets, Dornas proposal shows certain limitations in building a dialogical-liberating educational praxis which responds to contemporary challenges and needs. The proposal of this dissertation is to offer a critical reading of the pedagogical and theological tenets of Lécio Dornas proposal to the Sunday School of the Baptist Church, from the perspective of Paulo Freire and Juan Luis Segundo. Both will unveil a new approach to the Sunday School which intends to establish itself as praxis.